UTILIZATION OF WASTE COOKING OIL FROM CRACKER INDUSTRY INTO ECO-FRIENDLY CANDLES: PEMANFAATAN MINYAK JELANTAH INDUSTRI KERUPUK MENJADI LILIN RAMAH LINGKUNGAN - Bayu Wahyudi; Maya Arsanti; Mirza Bhilqis Jiratullah; Suci Paramita; Yasmin Yasmin (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: Waste cooking oil is a byproduct of food processing. If it is not managed properly, it can contribute to environmental pollution, particularly in food-processing MSMEs. Maulana Crackers, located in Purwodadi Village, generates used cooking oil that has not yet been converted into value-added products. Objective: This community service project aimed to enhance partners understanding waste cooking oil management and environmentally friendly candles as a value-added product. Method: The program was implemented by socialization and demonstration candle making using waste cooking oil. The program partnered with Maulana Crackers. At the end of the program, team conducted evaluation by discussions with employees to assess improvements their knowledge and practical skills. Results: Partners showed improved their knowledge and skills in purifying waste cooking oil and processing it into eco-friendly candles. In addition to minimizing waste cooking oil, the program also generated product candles with potential economic value. Conclusion: This program successfully promoted more effective waste cooking oil management, reduced negative environmental impact, and supported the development of eco-friendly products with potential economic value.